Antagonistic Impact of Lactic Acid Bacteria Isolates from the Natural Environment on the Growth of Toxigenic Fungi of the Fusarium Genus - Kluczyńska, Katarzyna Anna (Studia Oeconomica Posnaniensia, 2013)
The aim of this study is to determine the influence of lactic acid bacteria (LAB) isolates on the growth and degradation of the mycelium of selected toxin-producing fungi, which may lead to a reduction in the production of mycotoxins. Moulds of the Fusarium, Aspergillus and Penicillium genus pose a particular risk to the life and health of both people and animals because they produce mycotoxins. These are secondary metabolites of the fungi, the most dangerous of which include fumonisins, trichothecenes and zearalenone because of their mutagenic and carcinogenic properties. Toxigenic moulds are responsible for economic losses in crops, grain, food and livestock. These fungi are commonly found in crops, while the metabolites produced by them end up in animal feed and food. The modern trend among consumers is to choose organic products. As a result, chemical preservatives are becoming less and less popular and there is a greater interest in using microorganisms to reduce the growth of fungi. Bacteria exhibiting an inhibitory effect on the growth of pathogenic moulds could be widely used in various industries as biopreservatives and plant protection products. Experiments conducted in the Biochemistry and Microbiology laboratory in the Faculty of Commodity Science at the Poznań University of Economics confirmed the fungistatic influence of LAB on the growth of the analysed Fusarium moulds.